Efficacy and Safety of Epidermal Growth Factor Receptor (EGFR) Inhibitors Plus Antiangiogenic Agents as First-Line Treatments for Patients With Advanced EGFR-Mutated Non-small Cell Lung Cancer: A Meta-Analysis - Chen, Fei; Chen, Naifei; Yu, Yu; Cui, Jiuwei (Frontiers in Oncology, 2020)
Background: Tyrosine kinase inhibitors (TKIs) are standard treatment options for non-small-cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutations. Increasing clinical investigations have explored the value of EGFR-TKI antiangiogenic drug combination as the first-line EGFR-mutated NSCLC treatment. Materials and methods: We systematically searched PubMed, Cochrane Library, and Embase for randomized controlled trials (RCTs) investigating EGFR-TKI, with versus without antiangiogenic agents, in advanced EGFR-mutated NSCLC. The latest RCT presented orally at the 2019 European Society for Medical Oncology congress was obtained online. The endpoints include progression-free survival (PFS), overall survival (OS), objective response rate (ORR), disease control rates (DCR), and grade 3 or higher adverse events (AEs). Results: We included 7 articles on 5 trials with 1226 patients. All studies reached their primary study endpoints, PFS. EGFR-TKI plus angiogenesis inhibitor remarkably prolonged PFS, contrasted with EGFR-TKI monotherapy [hazard ratio (HR) = 0.59, 95% confidence interval (CI): 0.51-0.69, P = 0.000], while ORR [odds ratio (OR) = 1.17, 95% CI: 0.89-1.53, P = 0.258], DCR (OR = 1.36, 95% CI: 0.39-4.78, P = 0.635) and OS (HR = 0.94, 95% CI: 0.66-1.35, P = 0.745) didn’t make a difference between two groups. Overall, grade 3-5 AEs increased among combination therapy patients (OR = 5.772, 95% CI: 2.38-13.94, P = 0.000), specifically diarrhea incidence (OR = 2.51, 95% CI:1.21-5.23, P = 0.014), acneiform (OR = 1.815, 95% CI: 1.084-3.037, P = 0.023), hypertension (OR = 6.77, 95% CI: 3.62-12.66, P = 0.000), and proteinuria (OR = 13.48, 95% CI: 4.11-44.22, P = 0.000). Additionally, exons 19 deletions (HR = 0.61, 95% CI: 0.49-0.75, P = 0.000) and 21 Leu858Arg mutations (HR = 0.59, 95% CI: 0.47-0.73, P = 0.000) had almost equivalent PFS benefit when treated with double blocking therapy. Conclusions: EGFR-TKI plus anti-angiogenic drugs in EFGR-mutated NSCLC first-line setting yields striking PFS benefits, yet with higher AEs. EGFR-TKI plus antiangiogenic agent therapy may be considered a new option for advanced EGFR-mutated NSCLC patients.